Penentuan Menu Makanan Dalam Pemenuhan Kebutuhan Kalori Buruh Pabrik Dengan Analisis Detak Jantung - Muhammad Hermansyah; M. Imron Mas'ud (Jurnal Rekayasa Sistem Industri, 2018)
Many companies often pay less attention to the health of their employees during the work, it can seen from the number of employees exposed to the risk of diseases or health problems in retirement due to the imbalance between the needs of body and energy consumption that can lead to decreased productivity, especially labor-intensive companies one of them on the CV. X. The purpose of this study is to calculate the number of calories needed healthy body for employees of transport workers to regulate the pattern of food intake of the right transport workers so that caloric needs can be met. Data is collected by interview, observation and documentation study. The results showed that the work performed by transport workers was 1.5 hours including heavy work, 5 hours of moderate work and 1.5 hours of rest with an average caloric needs of 1253,601 cal / 8 hours of work, the body will experience a lack of calories when they work more or less about 6.5% (106,8576 cal / 8jam) of food they have eaten daily, then improved the food menu with an average of 1284,013 cal / 8 hours, an increase of 9.63% with the ratio of work productivity from before the improvement of 73.99% to 74.81%, resulting in an increase of 0.81%, implying on the convenience of laborers